Does Institutional Finance Matter for Agriculture? Evidence Using Panel Data from Uganda - Khandker, Shahidur R.; Koolwal, Gayatri B. (World Bank, Washington, DC, 2014)
Smallholder agriculture in many developing countries has remained largely self-financed. However, improved productivity for attaining greater food security requires better access to institutional credit. Past efforts to extend institutional credit to smaller farmers has failed for several reasons, including subsidized operation of government-aided credit schemes. Thus, recent efforts to expand credit for smallholder agriculture that rely on innovative credit delivery schemes at market prices have received much policy interest. However, thus far the impacts of these efforts are not fully understood. This study examines credit for smallholder agriculture in the context of Uganda, where agriculture is about 35 percent of gross domestic product, most farmers are smallholders, and the country has introduced policies since 2005 to extend credit access to the sector. The analysis uses newly available household panel data from Uganda for 2005-2006 and 2009-2010 to examine (a) whether credit effectively targets agriculture, by examining determinants of borrowing across different sources; (b) agricultural and nonagricultural determinants of supply and demand credit constraints among non-borrowers; and (c) the effects of borrowing and credit constraints on household income, consumption, and agricultural outcomes. The analysis finds that although not many households report borrowing specifically for agriculture, credit is fungible and agricultural outcomes do substantially improve with institutional borrowing, particularly microcredit. Among non-borrowers, supply and demand credit constraints have fallen considerably over the period, particularly in rural areas. Access to institutions and infrastructure play a strong role in alleviating the negative effect of credit constraints on welfare outcomes, as well as determining the source of lending among borrowing households.